2005
DOI: 10.1053/j.gastro.2005.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor: A Novel Target of the Wnt/β-Catenin Pathway in Liver

Abstract: Background & Aims-Wnt/β-catenin activation is observed in normal liver development, regeneration, and liver cancer. Our aim was to elucidate the regulation and mechanism of this pathway in liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
154
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(168 citation statements)
references
References 68 publications
13
154
0
1
Order By: Relevance
“…In addition, co-activation of EGFR and β-catenin is commonly seen in patients with HCC (Llovet et al, 2008). Some reports have demonstrated that Wnt/β-catenin activation could induce the EGFR activation in HCC (Tan et al, 2005). Interestingly, in the present study, we showed that EGFR activation induced β-catenin activation in HCC cell lines, highlighting the crosstalk between EGFR and Wnt pathways, which could be important for HCC tumorigenesis, progression and metastasis.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, co-activation of EGFR and β-catenin is commonly seen in patients with HCC (Llovet et al, 2008). Some reports have demonstrated that Wnt/β-catenin activation could induce the EGFR activation in HCC (Tan et al, 2005). Interestingly, in the present study, we showed that EGFR activation induced β-catenin activation in HCC cell lines, highlighting the crosstalk between EGFR and Wnt pathways, which could be important for HCC tumorigenesis, progression and metastasis.…”
Section: Discussionsupporting
confidence: 59%
“…Activation of the epidermal growth factor receptor has likewise recently been shown to activate h-catenin expression in liver carcinomas (50). It is therefore tempting to also speculate that the epidermal growth factor receptor might be a possible target for (-)-agelastatin A.…”
Section: Discussionmentioning
confidence: 98%
“…It potently inhibits the growth of murine and human cancer cell lines at low drug concentrations (11 -15) by mechanisms that have yet to be fully delineated. In this regard, (-)-agelastatin A potently retards the growth of a range of human tumor cell lines that include KB nasopharyngeal cancer cells (IC 50 , 0.075 Ag/mL), RT112/84 bladder carcinoma cells, SK-MEL-5 melanoma cells, HCT-116 colon carcinoma cells, and MDA-MB-435s breast cancer cells (15). In the latter four cell lines, (-)-agelastatin A is between 3 and 16 times more potent as an anticancer drug than the frontline chemotherapeutic agent cisplatin (15).…”
Section: Introductionmentioning
confidence: 99%
“…Recently published data on transgenic mice overexpressing b-catenin strengthen this assumption, as increased b-catenin expression leads to elevated EGFR levels in hepatocytes. Moreover, immunohistological analyses show a high correlation between the expression of nuclear/cytoplasmic b-catenin and EGFR in most hepatoblastomas (Tan et al, 2005).…”
Section: Cross-talk With Protumorigenic Factorsmentioning
confidence: 97%